Indicadores de qualidade na atuação do Conselho Municipal de Educação no âmbito do sistema de ensino de Cachoeira do Sul - RS - Hatsek, David Jorge Rodrigues (2019)
This professional master's research is linked to the Research Line for Policies and Management of Basic and Higher Education, of the Postgraduate Program in Public Policies and Educational Management, of the Federal University of Santa Maria, with the central theme of performance of the Municipal Council of Education in the scenario of the Municipal Education System. Its general objective is to analyze quality indicators and their implications for the performance of the Municipal Education Council of Cachoeira do Sul - RS within the scope of the Education System. For specific objectives, it prioritizes: understanding aspects of the democratization of education policies interrelated to the work of the Education Councils within the scope of the Municipal Teaching Systems; (ii) to map actions related to the quality performance of the municipal education council of Cachoeira do Sul; (iii) recognize quality perspectives that enhance the CME's dialogue within the scope of democratic management; (iv) produce a portfolio with quality indicators and their implications for the work of the Municipal Education Council of Cachoeira do Sul, RS. As for the methodological processes, these were based on the qualitative approach (FLICK, 2009), of the type of study that case (YIN, 2015) at the Municipal Education Council of the municipality of Cachoeira do Sul - RS, which adopted for data construction procedures the interview with the Secretary of Education; application of an online questionnaire to managers of the Municipal Education System within the scope of the CME and to municipal education counselors. Also, a documental analysis was performed as a technique that allows adding the dimension of time to the understanding of the social, in the same way that the state of knowledge research grounded the reflection in relation to the subject in question. Content analysis (BARDIM, 2007) was used for the intersection of the data produced. Based on the elements achieved in the research, the importance of a systemic view in the context of education is emphasized, especially at the municipal level, since this federated entity started to assume responsibilities for local education, establishing its own teaching system. And it is clear that in relation to the quality of education, it also encompasses extra-school and intra-school dimensions, with perspectives to suppose the different actors in the pedagogical dynamics, such as the teaching-learning processes, curricula, learning expectations, as well as the different extraschool factors that directly or indirectly interfere with educational results. The educational product, the result of this research, refers to a Portfolio that aims to provide quality indicators in order to guide the work developed with the municipal education council, with a view to contributing to the qualification of the performance of the collegiate in the field of performance of the Education System. Thus, the portfolio will allow a direction in the perspective of democratic management, of formation, being that in parallel it informs and trains the Municipal Council of Education about its strengths and attributions, but also, about the essential knowledge to the performance of its actors in the ambit of the system.